Customize apparel design online system: a conceptual solution - Ahmad Dahlan, Abdul Rahman; Mohd Ariffin, Siti Aminah; Saiful Sidek, Puteri Nur Sakeenah; Idris, Nor Izianti (Eclat Research Publication, 2016)
Nowadays, everything is done online. Many traditional services are made online to ease customers. This conceptual paper propose on a web-based online system that offers customers to customize and design their own apparels, shoes and bags and provide designers a platform to advertise their designs. While there are many websites that provide customize apparel design for normal size people, there are only few websites (especially in local) for big size and tall people. Few short interviews have been conducted to collect information about plus size and tall people; and their buying behavior. The key objectives of this customize apparel design online systems are to ease customers to choice, buy and design their own items such as pants, shirts, blouse and shoes in one stop center. The system is also specialize in customize plus size and tall people because according to the interviews most of them had difficulty when finding apparels and shoes. By using the system, each of the customers can have their own unique design based on their preferences. This system also provides a platform for designers to upload and share their design for free. For this conceptual paper, literature reviews and three integrated suite of tools are being used to helps understand the context and to helps create value for the business and the customer segments. The three integrated suite of tools are the nine blocks of business model canvas (BMC), the value proposition design (VPD) and the environment map (EM).